1996
DOI: 10.1111/j.1365-246x.1996.tb05264.x
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary evolution of the Corinth Rift and its implications for the Late Cenozoic evolution of the Aegean

Abstract: International audienceWe present geological and morphological observations at different scales to constrain rates of faulting and the distribution of deformation in the seismically active Aegean region. We focus first on the 130 km long Corinth Rift, an asymmetric graben where a flight of terraces of marine origin are uplifted. We show that the edges of the terraces lie in the footwall of the normal fault bounding the Corinth Rift and correspond to sea-level highstands of late Pleistocene age. Using a detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
796
7
58

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 676 publications
(948 citation statements)
references
References 102 publications
48
796
7
58
Order By: Relevance
“…Finally, additional extensional basins opened in the Peloponnese and along the eastern coast of the Hellenides, within the so-called Central Hellenides Shear Zone [Papanikolaou and Royden, 2007;Royden and Papanikolaou, 2011]. These basins include the Gulf of Corinth, which has accommodated ~15 km of N-S extension since the Pliocene (figure 3) [Armijo et al, 1996;Rohais et al, 2007;Jolivet et al, 2010b].…”
Section: Crete and The Peloponnesementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, additional extensional basins opened in the Peloponnese and along the eastern coast of the Hellenides, within the so-called Central Hellenides Shear Zone [Papanikolaou and Royden, 2007;Royden and Papanikolaou, 2011]. These basins include the Gulf of Corinth, which has accommodated ~15 km of N-S extension since the Pliocene (figure 3) [Armijo et al, 1996;Rohais et al, 2007;Jolivet et al, 2010b].…”
Section: Crete and The Peloponnesementioning
confidence: 99%
“…At the same time, extension ceased in the Cyclades and has localized at the edges of the Aegean domain, where highangle normal faulting has formed several grabens and half-grabens (figures 8w-y), such as in the Evvia island and the Corinth region (forming the Central Hellenic Shear Zone [Papanikolaou and Royden, 2007]), the Peloponnese, the Cretan Sea and the Menderes massif [Armijo et al, 1996;Royden and Papanikolaou, 2011;Pérouse et al, 2012]. This extensional tectonic regime has been accompanied in the Hellenides by a clockwise rotation of ~10° and ~23° north and south of the Central Hellenic Shear Zone [van Hinsbergen et al, 2005a;Bradley et al, 2013], increasing the curvature of the trench.…”
mentioning
confidence: 99%
“…King et al 1988;Weissel & Karner 1989;Armijo et al 1996;Schouten et al 2010). Further, the differences in rift morphology across spreading rates are generally well explained by rheological factors (i.e.…”
Section: O N C L U D I N G R E M a R K Smentioning
confidence: 92%
“…1a) [Armijo et al, 1999]. It has also been suggested that the propagating tip of the NAF reached the Corinth rift system in Greece around ~1 Ma [Armijo et al, 1996;Armijo et al, 1999]. Whether the westward propagation of the NAF is driven by the Arabia-Eurasia convergence and Anatolian block extrusion or by slab-pull mechanism associated with the Hellenic subduction zone (or by a combination of both processes) is subject of debate [e.g Armijo et al, 2003;Flérit et al, 2004;Sternai et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the NAF initiated at the Karlıova triple junction about ~10-13 Myrs ago [Şengör et al, 1985;Barka, 1992;Armijo et al, 1996;Armijo et al, 1999] and has grown by westward propagation over its nearly 2000 km-long trace (Fig. 1a) [Armijo et al, 1999].…”
Section: Introductionmentioning
confidence: 99%